Pengaruh Pembiayaan dan Arus Kas Terhadap Pengelolaan Modal Kerja - Putri, Ramadhani Wahyu Fitrilia; , Imronudin, S.E., M.Si., Ph.D (2017)
The purpose of this study was to determine whether there is influence between debt financing, equity financing and cash flow to the Working Capital on food and beverage company listed on the Indonesia Stock Exchange in the period 2013-2015. The population used in this study are all companies listed in Indonesia Stock Exchange issued by BEI period 2013-2015, while the sample in this study is a food and baverage company as many as 14 companies in the period 2013-2015. This study uses the variable Total Debt, Total Equity, Total Cash Flow and Working Capital. Methods of sample collection with a purposive sampling according to criteria that have been determined. Data that has been used is secondary data obtained from the Indonesia Stock Exchange (www.idx.co.id.) in the period 2013-2015. The collected data then analyzed by using regression method to test the hypothesis. The results showed that, variable total debt, total equity, and cash flow have significant positive and significant effect on working capital. It provides the knowledge that debt financing, equity financing and cash flow will be able to affect the working capital.